Avaliação da dureza superficial de cimentos resinosos utilizados na cimentação de pinos de fibra de vidro - Grande, Fernanda Zander (2006)
The purpose of this study was to investigate the interaction between two methods of adhesive systems activation (chemically cured and dual cured) and two methods of resin cements activation (chemically cured and dual cured) in Vickers microhardness values of resin cements, in differents depths of cure and differents distances of the adhesive systems used. There were 50 bovin inferior incisives which had their crowns transversaly crosscuted to use the root portion. The canal roots were prepared to the fiber posts cementation. The teeth were randomly divided in five groups: I) Adhesive system Prime & Bond 2.1 with Self Cure Activator and dual resin cement EnForce; II) Adhesive system Prime & Bond 2.1 and dual resin cement EnForce; III) ED Primer and chemically cured resin cement Panavia 21; IV) Adhesive system Clearfil SE Bond and chemically cured resin cement Panavia 21 e V) Adhesive system Prime & Bond 2.1 with Self Cure Activator and dual resin cement EnForce. In group V The EnForce wasn’t light-cured standing only with the chemically activation. After posts cementation the roots were cuted in 3 portions with 3 mm eatch (cervical, medium and apical) and after 7 days the specimens were tested. The specimens were divided in quadrants that recived 2 identations, one next the fiber post and other next the canal root surface. Data were submitted to threeway ANOVA and Tukey’s test. The application of these tests revealed statistically significant differences for the variables: group, position, region; interaction between group and position (p< 0,001), and interaction between group and region (p= 0,041). There weren’t, however, statistically significant differences interaction between position and region (p= 0.85). The conclusions were: the superficial hardness, independently of the kind of cement and adhesive system was always present in all regions of root canal; the chemically cured resin cement demonstrated the higher values of hardness; the factor depth of cure interfered in superficial hardness values in all groups, being more evident in GI and GII than GIII, GIV e GV; there was interference of adhesive systems in microhardness values for all groups, what can be observed in smaller values found next the adhesive systems. It was more evident in GIV that used the self-etched adhesive system and less evident in GIII that used ED Primer. The findings of this study demonstrates that the pH of adhesive systems inluences the microhardness values of resin cements.